Nilai-Nilai Transedental Dalam Pancasila Sebagai Kepribadian Bangsa Indonesia (Perspekspektif dari Seorang Muslim) - Basri Basri; Yulia Kurniaty; Johnny Krisnan (PAMALI: Pattimura Magister Law Review, 2021)
Introductioan: If we dig deeper, there is a compatibility between Islamic teachings and the values of Pancasila.Purposes of the Research: This study aims to analyze and discuss perspectives and attitudes in the context of Pancasila values that are practiced in social life.Methods of the Research: Answering the problems raised in this paper, the author conducts a literature study and observes what happens in social life.Results of the Research: The results of the study show that there is no longer any reason to contradict the teachings of Islam and Pancasila. The values of Pancasila are colored by the teachings of Islam itself and it is possible that the values of Pancasila are derived from Islamic teachings. Therefore, for Muslims, there is no need to question Pancasila as the basic philosophy of the Indonesian nation and state. For others, when there is a reaction from Muslims, for example there is an issue to replace Pancasila with another ideology, there is no need to react excessively, because it cannot happen and be carried out by Muslims. Such an attitude is basically just a reaction to what happened, where some Muslims are seen as contradicting the values of Pancasila as the personality of the Indonesian nation.